Abdominal emergencies in surgical oncology - Šefr, R; Zapletal, O; Krsička, P; Novotný, I; Pacal, M; Němec, L; Jedlička, V (Rozhledy v chirurgii, 2023)
INTRODUCTION: In general, abdominal emergencies are urgent situations that require a prompt and correct diagnosis and treatment. They involve a broad spectrum of diagnoses and can occur in all age groups. The situation is often modified in oncologic patients according to the extent and level of progression of the primary oncological disease. METHODS: A retrospective study was conducted to analyze the group of adult patients with abdominal emergencies treated in Masaryk Memorial Cancer Institute between 2011-2017. RESULTS: In total, 601 patients underwent emergency surgery during the 7-year period. The causes included gastrointestinal obstruction (43%), intra-abdominal inflammatory complications (33%) and bleeding (17%). Acute appendicitis or cholecystitis was the cause in only less than 4% of all patients. CONCLUSION: The problems of acute abdominal emergencies in oncologic patients are substantially different from those in the general population, particularly in terms of the causes where gastrointestinal obstruction is the leading cause.
Keywords: Intestinal Obstruction; acute abdomen; Emergencies; Retrospective Studies; Abdomen, Acute; břicho; Appendicitis; chirurgická onkologie; náhlé příhody; surgery; Adult; Abdomen; ileus; střevní obstrukce; akutní bolest břicha; retrospektivní studie; Humans; apendicitida; oncology; Surgical Oncology; intestinal obstruction; abdominal emergency; dospělí; lidé